Risk and economic burden of surgical site infection following spinal fusion in adults. (24th March 2022) - Edmiston, Charles E.; Leaper, David J.; Chitnis, Abhishek S.; Holy, Chantal E.; Chen, Brian Po-Han
Abstract: Background: Spinal fusion surgery (SFS) is one of the most common operations in the United States, >450, 000 SFSs are performed annually, incurring annual costs >10 billion. Objectives: We used a nationwide longitudinal database to accurately assess incidence and payments associated with management of postoperative infection following SFS. Methods: We conducted a retrospective, observational cohort analysis of 210, 019 patients undergoing SFS from 2014 to 2018 using IBM MarketScan commercial and Medicaid–Medicare databases. We assessed rates of superficial/deep incisional SSIs, from 3 to 180 days after surgery using Cox proportional hazard regression models. To evaluate adjusted payments for patients with/without SSIs, adjusted for inflation to 2019 Consumer Price Index, we used generalized linear regression models with log-link and γ distribution. Results: Overall, 6.6% of patients experienced an SSI, 1.7% superficial SSIs and 4.9% deep-incisional SSIs, with a median of 44 days to presentation for superficial SSIs and 28 days for deep-incisional SSIs. Selective risk factors included surgical approach, admission type, payer, and higher comorbidity score. Postoperative incremental commercial payments for patients with superficial SSI were 20, 800 at 6 months, 26, 937 at 12 months, and 32, 821 at 24 months; incremental payments for patients with deep-incisional SSI were 59, 766 at 6 months, 74, 875 at 12 months, and 93, 741 at 24 months. Corresponding incremental Medicare payments for patients with superficial incisional at 6, 12, 24-months were 11, 044, 17, 967, and 24, 096; while payments for patients with deep-infection were: 48, 662, 53, 757, and 73, 803 at 6, 12, 24-months. Conclusions: We identified a 4.9% rate of deep infection following SFS, with substantial payer burden. The findings suggest that the implementation of robust evidence-based surgical-care bundles to mitigate postoperative SFS infection is warranted.